O Professor Brincante e a Cultura Popular - Saberes e sabores na arte de ensinar - Silva, Marcelo Benigno Amorim e (2022)
The present work intends to reflect on how the experience with popular culture can stimulate processes of artistic creation and practices for education, through the performance of Professor Brincante. The text points out possibilities for dialogue and intersection between the research and practice of Professor Brincante, his concept and performance in the classroom and other educational spaces, while making a cartography of the "brincante" researcher for his research in conclusion.